Periacetabular Osteotomy Provides Higher Survivorship Than Rim Trimming for Acetabular Retroversion. Issue 4 (April 2017) - Zurmühle, Corinne A.; Anwander, Helen; Albers, Christoph E.; Hanke, Markus S.; Steppacher, Simon D.; Siebenrock, Klaus A.; Tannast, Moritz
Abstract: Background: Acetabular retroversion can cause impaction‐type femoroacetabular impingement leading to hip pain and osteoarthritis. It can be treated by anteverting periacetabular osteotomy (PAO) or acetabular rim trimming with refixation of the labrum. There is increasing evidence that acetabular retroversion is a rotational abnormality of the entire hemipelvis and not a focal overgrowth of the anterior acetabular wall, which favors an anteverting PAO. However, it is unknown if this larger procedure would be beneficial in terms of survivorship and Merle d'Aubigné scores in a midterm followup compared with rim trimming. Questions/purposes: We asked if anteverting PAO results in increased survivorship of the hip compared with rim trimming through a surgical hip dislocation in patients with symptomatic acetabular retroversion. Methods: We performed a retrospective, comparative study evaluating the midterm survivorship of two matched patient groups with symptomatic acetabular retroversion undergoing either anteverting PAO or acetabular rim trimming through a surgical hip dislocation. Acetabular retroversion was defined by a concomitantly present positive crossover, posterior wall, and ischial spine sign. A total of 279 hips underwent a surgical intervention for acetabular retroversion at our center between 1997 and 2012 (166 periacetabular osteotomies, 113 rim trimmings through surgical hip dislocation). A total of 99 patients (60%) were excluded from the PAO group and 56 patients (50%) from the rim trimming group because they had any of several prespecified conditions (eg, dysplasia or pediatric conditions 61 [37%] for the PAO group and two [2%] for the rim trimming group), matching (10 [6%]/10 [9%] hips), deficient records (10 [6%]/13 [12%] hips), or the patient declined or was lost to followup (18 [11%]/31 [27%] hips). This left 67 hips (57 patients) that underwent anteverting PAO and 57 hips (52 patients) that had acetabular rim trimming. The two groups did not differ in terms of age, sex, body mass index, preoperative ROM, preoperative Merle d'Aubigné‐Postel score, radiographic morphology of the acetabulum (except total and anterior acetabular coverage), alpha angle, Tönnis grade of osteoarthritis, and labral and chondral lesions on the preoperative MRI. During the period in question, we generally performed PAO from 1997 to 2003. With the availability of surgical hip dislocation and labral refixation, we generally performed rim trimming from 2004 to 2010. With growing knowledge of the underlying pathomorphology, anteverting PAOs became more common again around 2007 to 2008. A minimum followup of 2 years was required for this study. Failures were included at any time. The median followup for the anteverting PAO group was 9.5 years (range, 2‐17.4 years) and 6.8 years (range, 2.2‐10.5 years) for the rim trimming group (p < 0.001). Kaplan‐Meier survivorship analysis was performed using the following endpoints at 5 and 10 years: THA, radiographic progression of osteoarthritis by one Tönnis grade, and/or Merle d'Aubigné‐Postel score < 15 points. Results: Although the 5‐year survivorship of the two groups was not different with the numbers available (86% [95% confidence interval CI, 76%‐94%] for anteverting PAO versus 86% [95% CI, 76%‐96%] for acetabular rim trimming), we found increased survivorship at 10 years in hips undergoing anteverting PAO for acetabular retroversion (79% [95% CI, 68%‐90%]) compared with acetabular rim trimming (23% [95% CI, 6%‐40%]) at 10 years (p < 0.001). The drop in the survivorship curve for the acetabular rim trimming through surgical hip dislocation group started at Year 6. The main reason for failure was a decreased Merle d'Aubigné score. Conclusions: Anteverting PAO may be the more appropriate treatment for hips with substantial acetabular retroversion. This may be the result of reduction of an already smaller lunate surface of hips with acetabular retroversion through rim trimming. However, rim trimming may still benefit hips with acetabular retroversion in which only one or two of the three signs are positive. Future randomized studies should compare these treatments. Level of Evidence: Level III, therapeutic study.